When Female Feminists Falling in Love: Ideology, Media, and Practices - Karolus, Meike Lusye; Anisah, Laili Nur (Jurnal Perempuan, 2018)
Falling in love is a universal experience that cannot be bounded by racial, religious, ethnic, even ideological barriers. The experiences of falling in love and be in the relationships are also faced by female feminists. In the experiences of falling in love, female feminists often confront with tension between their consciousness in holding feminist ideology and their collective experiences influenced by patriarchal culture. Therefore, they have to compromise and negotiate in the relationship. This paper aims to explain contemplative experiences of female feminists who are falling in love in the patriarchal culture in the three areas of analysis: feminist thoughts which are build their consideration and consciousness, the influences of patriarchal media, and practices in the love relationship in everyday lives. This study is descriptive-qualitative using in-depth interview as a method toward female feminists from diverse background in Yogyakarta, Surabaya, and Jombang. The results are the concept of love from female feminists cannot be separated from the existence of their partners, the experiences and the reproduction of media about the concept of love, as well as the practices of female feminists’ relationships, which already creating the concept of love before entering relationships.